2017
DOI: 10.1097/md.0000000000008922
|View full text |Cite
|
Sign up to set email alerts
|

A recurrence-free survivor with chemotherapy-refractory small cell lung cancer after pneumonectomy

Abstract: Rationale:The optimal therapeutic regimen for chemotherapy-refractory and node-positive small-cell lung cancer (SCLC) is criticizable for the lack of evidence.Patient concerns:A patient with locally advanced SCLC was insensitive to the first-line chemotherapy of etoposide, irinotecan, and cisplatin.Diagnoses:The patient was diagnosed as SCLC with mediastinal lymph node metastasis by pathological staining.Interventions:Salvage pneumonectomy and systematic lymph node dissection combined with oral apatinib and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
(18 reference statements)
0
8
0
Order By: Relevance
“… 16 , 17 The current results also suggested that a lower dose might be a potential option in patients with advanced SCLC. Two recent reports described the use of apatinib combined with pneumonectomy or/and radiotherapy in two patients with relapsed SCLC, 18 , 19 while other studies reported on the use of apatinib as maintenance therapy in patients with stable SCLC after induction chemotherapy. 20 , 21 Low-dose apatinib might thus be a possible therapeutic choice in patients with advanced SCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 , 17 The current results also suggested that a lower dose might be a potential option in patients with advanced SCLC. Two recent reports described the use of apatinib combined with pneumonectomy or/and radiotherapy in two patients with relapsed SCLC, 18 , 19 while other studies reported on the use of apatinib as maintenance therapy in patients with stable SCLC after induction chemotherapy. 20 , 21 Low-dose apatinib might thus be a possible therapeutic choice in patients with advanced SCLC.…”
Section: Discussionmentioning
confidence: 99%
“… 14 17 We previously reported that low-dose apatinib (250 mg/day) monotherapy resulted in similar PFS to higher-dose apatinib (500–750 mg/day) in patients with NSCLC, 16 , 17 and was associated with fewer adverse effects in these studies. In a recent case report, apatinib (425 mg/day) combined with pneumonectomy and/or radiotherapy was used in two patients with relapsed SCLC, 18 , 19 and two other studies also reported on the use of apatinib as maintenance therapy in patients with stable SCLC after induction chemotherapy. 20 , 21 Another report used higher-dose apatinib (500 mg/day) in patients with extensive SCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the 5-year survival rate remains low at <7% overall; most patients survive for only <1 year after diagnosis (7). There had been few improvements in SCLC standard of care management in the decades prior to the IMpower133 results, which demonstrated survival benefit with the addition of the anti-PD-L1 agent atezolizumab to platinum-based chemotherapy for patients with extensive-stage SCLC (8).…”
Section: Introductionmentioning
confidence: 99%
“…This study highlighted the importance of performing lobectomy for resectable C-SCLC patients. Pan et al and Zeng et al also confirmed that surgical removal of the primary lesion in patients with SCLC is safe and effective, even when a larger extent of resection is necessary [20,21].…”
Section: Description Of the State Of Knowledgementioning
confidence: 86%
“…Of these, only manuscrpits dealing directly with surgical pulmonary resection in SCLC were selected. Based on these criteria, 14 publications were identified and included in the review [8][9][10][11][12][13][14][15][16][17][18][19][20][21](Tab. 1).…”
Section: Review Methodsmentioning
confidence: 99%